The parent as a "co-therapist" in the care of the minor: an ethical issue: Parent as a co-therapist of the minors - Alfano, Linda; Monteleone, Roberta; Petralia , Paolo; Ciliberti, Rosagemma (Medicina Historica, 2022)
Disease can represent a particularly complicated and sometimes traumatic event in the life of a child. The support and assistance of adults and the various reference figures (parents and health care personnel) who, with different functions and responsibilities, intervene in the care relationship, play a decisive role.The child in its complete entity must be at the center of the therapeutic intervention.The minor that must be taken care of, in fact, before being an ill person is a person with a history, a family with the experiences that characterize and shape his identity into specificity.The way in which health workers relate to parents and children affects significantly not only the course of care, but also the continuation of parental relationship and mental models that the child builds to formulate expectations about his future care experiences.To be able to adequately support the child, particular attention must be paid to promoting forms and methods of parental participation that are genuinely respectful, inclusive, and relevant.